Multiple Simultaneous Rare Distant Metastases as the Initial Presentation of Papillary Thyroid Carcinoma: A Case Report - Yang, Jing; Ma, Yu; Gong, Yanping; Gong, Rixiang; Li, Zhihui; Zhu, Jingqiang (Frontiers in Endocrinology, 2019)
Papillary thyroid carcinoma (PTC) commonly metastasizes to regional lymph nodes. However, they infrequently cause rare distant metastases (RDMs), with the exclusion of lungs and bone metastases. RDMs are seldom identified prior to a primary thyroid cancer diagnosis. Therefore, cases initially presenting with synchronously multiple RDMs from PTC are extremely infrequent. This is a rare case of a 48-year-old man with initial diaphragm, pancreatic, and liver tumors from PTC. Following resection of the tumors, an ultrasound-guided fine-needle aspiration (US-FNA) cytology of a mass in the thyroid’s left lobe revealed PTC. After postoperative recovery for more than 4 months, physical examination identified an irregular large nodule in the thyroid's isthmus and left lobe, a swollen lymph node in the left neck, and a mass in the right parotid gland. Ultrasound reexamination revealed numerous hypoechoic masses as follows: one in the thyroid's isthmus and entire left lobe (7.3 × 5.9 × 5.1 cm) and multiple in the thyroid's right lobe (0.2–0.3 cm). Ultrasound examination also showed several swollen lymph nodes in the left neck, a mass in the left gluteus maximus, and several masses in both the bilateral parotid and salivary region. The US-FNA’s pathological examination confirmed metastatic PTCs in the left gluteus maximus and bilaterally located in the parotid and salivary gland. 18-fluorodeoxyglucose positron-emission tomography and computed tomography scan revealed abnormal uptakes in numerous locations (e.g., the thyroid's isthmus and left lobe, bilateral parotid gland, subcutaneous tissues, etc.). The patient underwent palliative therapy, including total thyroidectomy, bilateral central neck dissection, left lateral neck dissection, and excision of the bilateral parotid and salivary gland. A whole-body scan post-therapeutic radioactive iodine ablation showed exclusive thyroid bed uptake. Subsequently, the patient underwent continuous thyroid stimulating hormone repression therapy and was treated with lenvatinib chemotherapy for approximately 8 months. The primary thyroid tumor, pancreatic metastasis, and cervical lymph node metastasis were both positive for BRAFV600E and TERT promoter (C288T) mutations. After 13 months of follow-up, the patient is currently in stable clinical conditions. In conclusion, the present case is an extremely rare occurrence of simultaneous multiple RDMs from PTC as the initial presentation.